2021
DOI: 10.1111/apa.16178
|View full text |Cite
|
Sign up to set email alerts
|

Acute abdomen in multisystem inflammatory syndrome in children: A systematic review

Abstract: Aim Multisystem inflammatory syndrome in children (MIS‐C), a rare severe complication of SARS‐CoV‐2 infection, has been recently reported to mimic acute abdomen and lead to surgical interventions, posing challenges for clinicians. In this systematic review, we evaluated the rate of acute abdomen and abdominal surgical emergencies in children with MIS‐C. Methods Systematic review of all MIS‐C cases presented with acute abdomen. Results A total of 385 patients with MIS‐C, from 38 studies, were included. Gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 45 publications
6
43
0
5
Order By: Relevance
“…As in our case, among all these values, increased inflammatory markers, lymphopenia and hypoalbuminemia are common findings in patients with gastrointestinal symptoms (4,6). Reviewing abdominal imaging in MIS-C patients, common US findings are ascites, acalculous cholecystitis, bowel wall thickening and mesenteric adenitis (4,(6)(7)(8). Moreover, in a systematic review Rouva et al reported an incidence of 30% of acute abdomen among MIS-C patient with gastrointestinal symptoms.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…As in our case, among all these values, increased inflammatory markers, lymphopenia and hypoalbuminemia are common findings in patients with gastrointestinal symptoms (4,6). Reviewing abdominal imaging in MIS-C patients, common US findings are ascites, acalculous cholecystitis, bowel wall thickening and mesenteric adenitis (4,(6)(7)(8). Moreover, in a systematic review Rouva et al reported an incidence of 30% of acute abdomen among MIS-C patient with gastrointestinal symptoms.…”
Section: Discussionsupporting
confidence: 63%
“…Despite gastrointestinal symptoms (abdominal pain, emesis and diarrhea) are common features in MIS-C patients, only in a few cases these manifestations resemble an acute appendicitis ( 5 7 , 13 15 ). Moreover, when these manifestations precede other organ involvement a differential diagnosis between inflammatory bowel disease, abdominal surgical conditions or severe infections could be difficult ( 13 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most reports, fever and abdominal or gastrointestinal symptoms (abdominal pain, diarrhea, and vomiting) are described as the most frequent ( 46 , 48 , 53 ). On the other hand, the presenting symptoms of MIS-C may mimic an acute abdomen, including acute appendicitis, as shown in a multicenter Latin-American study, in which 34/1,010 (3.3%) patients with COVID-19 and MIS-C had an intraoperative diagnosis of appendicitis ( 55 ). Furthermore, a systematic review of abdominal pain in MIS-C found an incidence of acute abdomen of 19%, which was non-surgical in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review evaluating 385 cases of MIS-C, gastrointestinal symptoms were a feature of a patient’s presentation in 60.5 per cent of cases. 4 Although many of these patients were eventually diagnosed with a non-surgical pathology such as mesenteric adenitis or terminal ileitis, 48.6 per cent who presented with an ‘acute abdomen’ underwent a laparotomy, 51.4 per cent of which were negative. A surgical pathology such as acute appendicitis or obstructive ileus were confirmed in 23.6 per cent of cases, suggesting that relying on clinical findings alone might be insufficient while we better understand this emerging disease process.…”
mentioning
confidence: 99%